Regional development and the new economy - Andrew Gillespie; Ranald Richardson; James Cornford (EIB Papers, 2001)
In this paper we are concerned with the implications of information and communications technologies (ICTs), and the so-called 'new economy' with which they are associated, for regional development. As such, we are concerned particularly with examining the ways in which ICTs may 'change the balance' between centralising and decentralising dynamics in the space-economy. A number of starkly different spatial expressions of the 'new economy' can be postulated, making our task a necessary one to undertake, in that the overall outcomes in terms of spatial organisation and regional development are not self-evident.
Keywords: 330; Regionales Wachstum; Informationstechnik; Großbritannien; New Economy